1. (3 + xz)(–3 + xz)
2. (y² – xy)(y² + xy)
3. (64y2 + x2)(–x2 + 64y2)
Explanation
The difference of 2 squares is in the form (a+b)(a-c).
(3 + xz)(–3 + xz) = (3 + xz)(xz -3)
= (xz + 3)(xz - 3)
= x²y²-3xy+3xy-9
=x²y² - 3²
(y² – xy)(y² + xy) = y⁴+xy³-xy³-x²y²
= y⁴ - x²y²
(64y2 + x2)(–x2 + 64y2)= (64y²+x²)(64y²-x²)
= 4096y⁴-64y²x²+64y²x²-x⁴
= 4096y⁴ - x⁴
Answer:
Solution (7,1)
Step-by-step explanation:
Use the elimination method
x + y=8
x - y=6
--------------Add
2x = 14
x = 7
Substitute x = 7 into x + y=8
7 + y=8
y = 8 - 7
y = 1
Solution (7,1)
Answer:
10/3 liters
Step-by-step explanation:
Divide (4/3) by 2, then multiply by 5
Answer:
b. both functions have a negative slope
Step-by-step explanation:
The given function is
![f(x)=-6x-21](https://tex.z-dn.net/?f=f%28x%29%3D-6x-21)
This function is of the form
, where
is the slope and
is the y-intercept.
We can also determine the slope of the function in the table using any two points, say
.
The slope formula is given by,
.
If
, then,
![m=\frac{6-7}{2-0}](https://tex.z-dn.net/?f=m%3D%5Cfrac%7B6-7%7D%7B2-0%7D)
.
We can see that both functions have a negative slope.
The correct answer is B.